2014
DOI: 10.1371/journal.pone.0116174
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation after Presyncope by Lower Body Negative Pressure in Humans

Abstract: Central hypovolemia elevates hemostatic activity which is essential for preventing exsanguination after trauma, but platelet activation to central hypovolemia has not been described. We hypothesized that central hypovolemia induced by lower body negative pressure (LBNP) activates platelets. Eight healthy subjects were exposed to progressive central hypovolemia by LBNP until presyncope. At baseline and 5 min after presyncope, hemostatic activity of venous blood was evaluated by flow cytometry, thrombelastograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 31 publications
7
20
2
Order By: Relevance
“…Consistent with this idea, platelet activation, demonstrated by increased exposure of active glycoprotein 2b/3a, has been shown after LBNP (37). We observed an increase in platelet count after both LBNP and BL.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this idea, platelet activation, demonstrated by increased exposure of active glycoprotein 2b/3a, has been shown after LBNP (37). We observed an increase in platelet count after both LBNP and BL.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, shock promotes fibrinolysis from non-trauma patients with pre hospital circulatory collapse, who have a high incidence of hyperfibrinolysis (32). This is also evident in healthy subjects undergoing mimicked shock with lower body blood pooling that increase their tPA levels 10 fold from baseline (33). TEG also provides additional indices of coagulation abnormality, which can guide blood product resuscitation beyond plasma.…”
Section: Discussionmentioning
confidence: 85%
“…In both cases, the blood levels of von Willebrand factor and factor VIII increased dramatically after fainting. These findings could be replicated in two experimental studies [9,14] in normal subjects who suffered vasovagal pre-syncope during LBNP. Moreover, Zaar et al [14] demonstrated platelet activation and a significant acceleration of coagulation after LBNP-induced pre-syncope.…”
mentioning
confidence: 59%
“…These findings could be replicated in two experimental studies [9,14] in normal subjects who suffered vasovagal pre-syncope during LBNP. Moreover, Zaar et al [14] demonstrated platelet activation and a significant acceleration of coagulation after LBNP-induced pre-syncope. A reduction in coagulation time is even present during lower levels of LBNP-induced decreases of central venous pressure (CVP) insufficient to induce presyncope.…”
mentioning
confidence: 59%